The Influence of Transformational Leadership of Principals and Teacher Work Discipline on Teacher Work Productivity - Idham; Budi Hart (Managere: Indonesian Journal of Educational Management, 2025)
Teacher productivity will be created in accordance with the goals that have been planned through the leadership style, work discipline of transformational principals and teachers in creating increased teacher productivity, leadership needs, leadership roles, transformational principals, and established teacher work discipline in schools. The research method used is a survey method with a quantitative approach, while the data collection technique is a questionnaire. The results showed that the transformational leadership of school principals had a significant influence on teacher productivity while the contribution between variable X1 to Y had an effect of 41.6% while the influence of teacher discipline X2 on teacher productivity (Y) was 45.4%. Based on the results of the determination of X1 and X2 to Y obtained simultaneously of 0.590 from the regression equation Ŷ = R2 X 100% or 0.590 X 100% = 59% while the remaining 41% is influenced by other variables.